Factors Affecting Field Rice Production (Oryza et al.) in East Barito Regency, Central Kalimantan Province - Barbara, Betrixia; Dewi Nopembereni, Eti; Prajawahyudo, Tri; K.P. Asiaka, Fandi; Pordamantra, Pordamantra; Yuliana Eka Sintha, Tri; Yuprin, Yuprin (Journal of World Science, 2023)
This study aims to determine the factors that influence the production of field rice farming in Kalamus Village, Paku District, East Barito Regency. The research location is in Kalamus Village, Paku District, East Barito Regency. Location determination using a purposive sampling method. The sampling technique in this study uses the Saturated Sampling Technique, where the number of samples is equal to the total population, namely 35 farmers. Data analysis using multiple linear regression. The results showed that field rice farming activities were still carried out subsistence to support food security for farmers and their families. Based on the results of multiple linear regression analysis, partially, the factors that significantly influence the production of upland rice are planting area, seeds, and labor. In contrast, the pesticide factor has no significant effect on production. Swid management has been carried out permanently or no longer moving, and pesticides have been used in clearing land and handling pests and diseases of Paddy Field plants. So it can be concluded that although the results of the Multiple Regression Test show that pesticides do not have a significant effect on the production of upland rice, this may occur because, in general, the cultivators did not carry out maintenance on their land, only relying on the generosity of nature. Still, now with permanent land conditions, without burning, farmers must be able to manage their land with technology, especially clearing land and weeds, as well as pests and diseases using pesticides.